Identification of selection signals by large-scale whole-genome resequencing of cashmere goats. Issue 1 (December 2017) - Li, Xiaokai; Su, Rui; Wan, Wenting; Zhang, Wenguang; Jiang, Huaizhi; Qiao, Xian; Fan, Yixing; Zhang, Yanjun; Wang, Ruijun; Liu, Zhihong; Wang, Zhiying; Liu, Bin; et al.
Abstract Inner Mongolia and Liaoning cashmere goats are two outstanding Chinese multipurpose breeds that adapt well to the semi-arid temperate grassland. These two breeds are characterized by their soft cashmere fibers, thus making them great models to identify genomic regions that are associated with cashmere fiber traits. Whole-genome sequencing of 70 cashmere goats produced more than 5.52 million single-nucleotide polymorphisms and 710, 600 short insertions and deletions. Further analysis of these genetic variants showed some population-specific molecular markers for the two cashmere goat breeds that are otherwise phenotypically similar. By analyzingF ST and θπ outlier values, we identified 135 genomic regions that were associated with cashmere fiber traits within the cashmere goat populations. These selected genomic regions contained genes, which are potential involved in the production of cashmere fiber, such asFGF5, SGK3, IGFBP7, OXTR, andROCK1 . Gene ontology enrichment analysis of identified short insertions and deletions also showed enrichment in keratinocyte differentiation and epidermal cell differentiation. These findings demonstrate that this genomic resource will facilitate the breeding of cashmere goat and otherCapra species in future.